Mediating role of work-family psychological contract in relationships between personality and work-family factors, and job satification in selected utility service organizations - Mat Jusoh, Mardhiah (2014)
Most studies have examined the direct relationship between personality factors and work-family factors with job satisfaction. However, research on the role of work-family psychological contract as a mediator in the relationships between personality factors and job satisfaction, and in the relationship between work-family factors and job satisfaction is less examined. This study tested a mediation model consisting of personality factors and work-family factors as independent variables, job satisfaction as dependent variable and work-family psychological contract as the mediator. The objectives of the study are to determine (i) the mediating effect of work-family psychological contract on the relationship between self-esteem and job satisfaction, (ii) the mediating effect of work-family psychological contract on the relationship between locus of control and job satisfaction, (iii) the mediating effect of work-family psychological contract on the relationship between positive affectivity and job satisfaction, (iv) the mediating effect of work-family psychological contract on the relationship between negative affectivity and job satisfaction, (v) the mediating effect of work-family psychological contract on the relationship between work interference with family and job satisfaction, and (vi) the mediating effect of work-family psychological contract on the relationship between work-family facilitation and job satisfaction. This study used correlation research design to discover the direction and strength of the relationship among variables. This research used the structural equation modelling analysis to achieve the study objectives. There are six independent variables (selfesteem, locus of control, positive affectivity, negative affectivity, work interference with family and work-family facilitation), one dependent variable (job satisfaction) and one mediator (work-family psychological contract). This study point out that personality factors and work-family factors affect job satisfaction directly and indirectly. Indirect effects explain the relationship between independent variables (personality factors and work-family factors) and job satisfaction through the work-family psychological contract as a mediator. Meanwhile, direct effect describes the relationship between independent variables (personality factors and work-family factors) and job satisfaction. The sample of this study consisted of executives and professionals in private organizations in the Klang Valley. Data were gathered from 230 employees of private organizations using self-administered questionnaires. The drop and collect method was used to collect data from the sample, with the assistance from human resource department of particular organizations. The random sampling procedure was used to pick the respondent for this study. This study extends the existing psychological contract literature and hopes to contribute additional insights to psychological contract and work-family studies especially in Malaysia. For the field of human resource development this study will yield additional insights to the relationship between work-family psychological contract and job satisfaction among employees and employers. Furthermore, this study hopes to provide knowledge especially for private organizations to give attention personality and workfamily factors which could influence work-family psychological contract fulfilment and thereby provide a practical means to improve job satisfaction among employees.